Immunogenicity and Safety of 10-valent Pneumococcal Nontypeable Haemophilus influenzae Protein D Conjugate Vaccine (PHiD-CV) Administered to Children With Sickle Cell Disease Between 8 Weeks and 2 Years of Age: A Phase III, Open, Controlled Study. Issue 5 (May 2017) - Sirima, Sodiomon B.; Tiono, Alfred; Gansané, Zakaria; Siribié, Mohamadou; Zongo, Angèle; Ouédraogo, Alphonse; François, Nancy; Strezova, Ana; Dobbelaere, Kurt; Borys, Dorota
Abstract : Background: Immunogenicity, safety and reactogenicity of the 10-valent pneumococcal nontypeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) were evaluated in children with sickle cell disease (SCD), who are at increased risk for infections. Methods: In this phase III, open-label, single-center, controlled study in Burkina Faso (NCT01175083), children with SCD (S) or without SCD (NS) were assigned to 6 groups (N = 300): children 8–11 weeks of age (<6 months; <6S and <6NS groups) received 3 primary doses and a booster dose of PHiD-CV coadministered with routine childhood vaccines; children 7–11 months of age (7-11S and 7-11NS groups) received 2 primary doses and a booster dose of PHiD-CV; children 12–23 months of age (12-23S and 12-23NS groups) received 2 catch-up doses of PHiD-CV. Pneumococcal antibody responses were measured using 22F-inhibition enzyme-linked immunosorbent assay and functional opsonophagocytic activity. Responses to other antigens were measured by enzyme-linked immunosorbent assay. Adverse events were recorded. Results: One month postprimary vaccination, for each vaccine serotype ≥98% of infants in the <6S and <6NS groups had antibody concentrations ≥0.2 µg/mL, except for 6B (≥85%) and 23F (≥89%). Immune responses to PHiD-CV after age-appropriate vaccination in children <2 years did not appear influenced by SCD. All infants were seroprotected/seropositive for diphtheria, tetanus and Bordetella pertussis antigens postprimary and booster vaccination. Safety and reactogenicity profiles were similar in children with or without SCD. Conclusions: PHiD-CV was immunogenic with an acceptable safety profile in children with and without SCD starting vaccination at 8 weeks to 23 months of age. Abstract : Supplemental Digital Content is available in the text.